A Note on Farmer's Consumption and Its Stabilizing Nature - Wang, Cheng-Hsien (The Review of Economics and Statistics, 1950)
IN the August I947 issue of this REVIEW, Mr. Willard W. Cochrane, presenting a summary of his study about family budgets among Corn Belt farmers in the United States,' concluded that two different forces emanate from the income-outlay behavior of farm families: an explosive force associated with expenditures for capital and a stabilizing force associated with expenditures for family living.2 The character of farmers' expenditures as a whole, however, was not ascertained. Furthermore, the procedure seems doubtful.